Students’ Difficulties in Learning English Vocabulary and Solutions for Learning Strategies at Junior High School - Tirsa Esevania; Jamiluddin Jamiluddin; Muhammad Arid; Mawardin M Said (Journal of English Language and Education, 2026)
Vocabulary mastery is fundamental to English language learning because it supports the development of listening, speaking, reading, and writing skills. Although numerous studies have examined vocabulary learning strategies, limited attention has been given to how junior high school EFL students simultaneously experience vocabulary learning difficulties and employ strategies to overcome them within their actual classroom context. This study aimed to identify students’ vocabulary learning difficulties and the strategies they used to address them. A qualitative descriptive design was employed involving 23 eighth-grade students and one English teacher at SMP Negeri 14 Sigi. Data were collected through open-ended questionnaires and semi-structured interviews and analyzed using the Miles and Huberman interactive model. The findings revealed that students experienced difficulties in vocabulary retention, contextual understanding, pronunciation, sentence construction, and speaking confidence. To cope with these challenges, they primarily used memorization, translation, repetition, and digital learning tools. The study concludes that integrating interactive, contextual, and technology-supported vocabulary instruction can enhance students’ vocabulary mastery, learning engagement, and confidence while providing practical insights for improving vocabulary instruction in junior high school EFL classrooms.